A avaliação enquanto uma função arquivística: o desenvolvimento e aplicação no contexto brasileiro - MORAIS, Ayrton Lima (2017)
The paper addresses the evaluation of documents as a function to archives in construction, the conceptual aspects, the resulting product of this function, and the development and application in the Brazilian context. Understanding that the preparation of table of temporality is the product of the assessment documents, we tried to use as example existing tables in Brazil, we constructed a comparative analysis between each table highlighting the points where they converge and diverge, as well as, the functionality of the table, in order to show what practical on the national scene results from the evaluation. The research has as general objective to analyze the assessment documents while archiving function, presenting concepts and some aspects related to the Brazilian context and its visualization in practice, seeking to achieve this objective was performed a theoretical research literature of qualitative, where data collection took place from a review of the literature. The evaluation has as its goal the assigning values to documents that determines the proper disposal of the same, however, in the course of the research it was established that the way occurs this allocation of value that also determines the periods of custody of the documentation is not made clear, especially when we are talking about public institutions, in this sense the research makes some comments and suggestions.